2007
DOI: 10.1245/s10434-007-9425-5
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Oxidation Protein Products, Ferrous Oxidation in Xylenol Orange, and Malondialdehyde Levels in Thyroid Cancer

Abstract: In conclusion, all of AOPP, FOX, and MDA levels that are markers of protein oxidation and lipid hyperoxidation may induce thyroid cancer development and begin to decrease after thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…The concentration of trace elements in the thyroid gland is higher than in other tissues (7) and it has been shown that the thyroid hormones do infl uence the metabolism of these elements (2,(8)(9)(10). Furthermore, changes in these elements were associated with development of goiter and other thyroid pathologies including cancer (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of trace elements in the thyroid gland is higher than in other tissues (7) and it has been shown that the thyroid hormones do infl uence the metabolism of these elements (2,(8)(9)(10). Furthermore, changes in these elements were associated with development of goiter and other thyroid pathologies including cancer (7).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, changes in these elements were associated with development of goiter and other thyroid pathologies including cancer (7). Trace elements are essential micro-nutrients both for humans and other organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Acute and chronic loud noise contact generates extreme free radicals and reason disorders that involve extraauditory body part such as neural cells, endocrine functions and cardiovascular homeostasis [17]. Accumulation of AOPPs has been described in many pathologie [18][19][20], also those connected with impaired carbohydrate metabolism [18,21]. These products create as a result of the action of free radicals on proteins and may act as inflammatory mediators triggering the oxidative "ignition" of neutrophiles, monocytes and T lymphocytes thus leading to up regulation and excessive motivation of dendritic cells [22].…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative damage to cells and tissues could be manifested through the serum level of MDA as the lipid peroxidation marker (8) level in post-thyroidectomy was significantly lower compared to pre-thyroidectomy, and the healthy subjects still showed significantly higher levels of MDA. Higher levels of MDA could be attributed to the increased production of free radicals, exceeding the capacities of the antioxidant enzymes (23).…”
Section: Discussionmentioning
confidence: 99%